Reproducible planar heterojunction solar cells based on one-step solution-processed methylammonium lead halide perovskites - Bai, S; Sakai, N; Zhang, W; Wang, Z; Wang, J; Gao, F; Snaith, H (American Chemical Society, 2016)
Metal halide perovskites have been demonstrated as one of the most promising materials for low-cost and high-performance photovoltaic applications. However, due to the susceptible crystallization process of perovskite films on planar substrates and the high sensitivity of the physical and optoelectronic nature of the internal interfaces within the devices, researchers in different laboratories still experience poor reproducibility in fabricating efficient perovskite solar cells with planar heterojunction device structures. In this methods paper, we present detailed information on the reagents, equipment, and procedures for the fabrication of planar perovskite solar cells in both “regular” n-i-p and “inverted” p-i-n architectures based on one-step solution-processed methylammonium lead triiodide (MAPbI3) perovskite films. We discuss key parameters affecting the crystallization of perovskite and the device interfaces. This methods paper will provide a guideline for the reproducible fabrication of planar heterojunction solar cells based on MAPbI3perovskite films. We believe that the shared experience on MA-based perovskite films and planar solar cells will be also useful for the optimization process of perovskites with varied compositions and other emerging perovskite-based optoelectronic devices.